An Overview of Cognitive Disturbances in Multiple Sclerosis, Progression and Management (Global Journal of Medical Research, 2020)
This review will concentrate on discovery of cognitive disability in MS and available treatment options to decrease symptoms. We performed a search using electronic databases; MEDLINE, and EMBASE, through October, 2019. Search strategies used following MeSH terms in searching: "Multiple Sclerosis", "Cognitive", "screening", "management". Cognitive dysfunctions are constant signs and symptoms of multiple sclerosis (MS) and occur in up to 65% of individuals. Especially memory, attention, executive and visual constructive functions suffer. These problems strongly impact individuals' capacity to work, social relationships, and quality of life. Signs and symptoms of physical disabilities can occur separately. Cognitive disorders are clear indicators of MS progression, since they stand for highly complicated features that depend on the integrity of the neuronal networks. Yet, severe dementia is relatively uncommon.